Liturgi Epifani Sebagai Manifestasi Kehadiran Kristus: Suatu Kajian Teologis- Liturgis Dalam Tradisi HKBP - Roymandani Manurung; Tumpal Samuel Silitonga (Sekolah Tinggi Teologi Sriwijaya, 2026)
This study explores the theological and liturgical meaning of the Epiphany celebration as a manifestation of Christ’s presence within the tradition of the Huria Kristen Batak Protestan (HKBP). In the wider Christian tradition, Epiphany is understood as the revelation of Christ to the nations seen in the visit of the Magi, His baptism in the Jordan, and His first miracle at Cana. Yet within the context of HKBP, this celebration tends to receive less emphasis compared to Christmas, Easter, and Pentecost. Using a qualitative approach, this research draws on literature review and interviews with two pastors and two congregational members. The analysis applies a liturgical hermeneutical framework based on the HKBP Agenda. The findings indicate that, theologically, Epiphany affirms Christ as the Light for all nations. However, in practice, its meaning has not been deeply rooted in the spiritual awareness of the congregation. An examination of HKBP’s liturgical texts reveals a worship structure rich in theological symbols that proclaim Christ’s presence. Therefore, a renewed understanding of Epiphany is needed, one that is nurtured through liturgical education, the enrichment of worship symbols, and a stronger emphasis on Christ’s universal mission in the life of the church community.